2009
DOI: 10.1111/j.1541-0420.2008.01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Factor Selection and Collapsing Levels in ANOVA

Abstract: Summary. When performing an Analysis of Variance, the investigator often has two main goals: to determine which of the factors have a significant effect on the response, and to detect differences among the levels of the significant factors. Level comparisons are done via a posthoc analysis based on pairwise differences. This paper proposes a novel constrained regression approach to simultaneously accomplish both goals via shrinkage within a single automated procedure. The form of this shrinkage has the ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 22 publications
5
102
0
Order By: Relevance
“…This raises a number of issues, including how to form sensible subgroup combinations and, from a technical standpoint, how to weight each of the effect estimates to produce a combined estimate (see e.g., [42,43]). It is beyond the scope of this article to examine this area in detail, but in some additional analyses in which estimates arising from several subgroups in our case-study were combined based on clinical similarity, we found some evidence of an above average treatment effect in the combined subpopulation.…”
Section: Discussionmentioning
confidence: 99%
“…This raises a number of issues, including how to form sensible subgroup combinations and, from a technical standpoint, how to weight each of the effect estimates to produce a combined estimate (see e.g., [42,43]). It is beyond the scope of this article to examine this area in detail, but in some additional analyses in which estimates arising from several subgroups in our case-study were combined based on clinical similarity, we found some evidence of an above average treatment effect in the combined subpopulation.…”
Section: Discussionmentioning
confidence: 99%
“…These tests allow for the comparison of all haplotypes to determine the effect structure. Following the idea of the penalized approach to ANOVA9, we estimate the effects ( γ 0 , γ , β ) by ( γ̂ 0 , γ̂ , β̂ ), which is the minimizer of…”
Section: Methodsmentioning
confidence: 99%
“…Including the nostril factor in the model allowed for control of the variability of the response variable area among different cadavers. These characteristics of the repeated measures model allowed the comparisons among the means of the response variable under the different treatments to be highly accurate [14][15][16][17] .…”
Section: Nostril Cross-section Area Evaluation and Statistical Analysismentioning
confidence: 99%